Individual and contextual factors related to dental caries in underprivileged Brazilian adolescents - Vazquez, Fabiana de Lima; Cortellazzi, Karine Laura; Kaieda, Armando Koichiro; Bulgareli, Jaqueline Vilela; Mialhe, Fábio Luiz; Ambrosano, Gláucia Maria Bovi; Tagliaferro, Elaine Pereira da Silva [UNESP]; Guerra, Luciane Miranda; Meneghim, Marcelo de Castro; Pereira, Antonio Carlos (My University, 2015)
Background: Investigate the individual and contextual variables related to caries in underprivileged adolescents, and the disparity in distribution of the disease. Methods: Cross-sectional analytical study, conducted in the city of Piracicaba, SP, Brazil, in 2012. The probabilistic sample was composed of 1,179 adolescents from 15–19 years of age, randomly selected from 21 state schools and 34 Primary Health Units – Family Health (PHU-FH). The dependent variables studied were number of decayed teeth and caries experience (DMFT). The independent variables were classified into individual (clinical, sociodemographic, psychosocial, self-perception, impact on oral health, access to services, and quality of life) and contextual (social exclusion index, total number of residents in suburb, literacy rate, and the following variables given in percentages: residences in the home ownership category, provision of domestic sewerage, trash collection, families with income of over 1 minimum wage per month, and families without monthly income) variables. The multilevel regression model was estimated by the PROC GLIMMIX (Generalized Linear Models-Mixed) procedure, considering the individual variables as Level 1 and the contextual variables of the suburbs as Level 2. Adjustment of the model was evaluated by −2 Res Log Likelihood with α = 0.05. Results: As regards the individual variables, adolescents who declared having a prison inmate in the Family and resided in homes with a larger number of persons, showed a higher number of decayed teeth. There were a larger number of decayed teeth, a higher DMFT value, and worse self-perception as regards the health of their teeth and mouth. Other variables, such as being of the female gender, age and time since last visit to the dentist were related to the DMFT index. As regards the contextual variables, the DMFT was lower in suburbs with greater access to domestic sewage, and the number of decayed teeth was higher in suburbs with the worst social exclusion indices. Conclusion: Individual and contextual variables were associated with the presence of caries and DMFT index in underprivileged adolescents, indicating that they must be taken into consideration in the formulation of policies directed towards oral health promotion and prevention activities in this group.
Keywords: Dental caries; Risk assessment; Social vulnerability; Adolescent behavior